Deutsch als Fach- und Fremdsprache in den Rechtswissenschaften - Engberg, Jan; Meyer, Almut (De Gruyter, 2025)
This article deals with the teaching of German as a foreign language of German as a legal language to law students and translation students. On the basis of recent developments in specialised communication research a focus on the acquisition of specialised knowledge relevant to understanding is proposed
and justified. Subsequently, the implementation of such a focus on teaching concepts and also presents a relevant cultural studies model of interpretation.interpretation model is also presented.
Handbuch Deutsch als Fach- und Fremdsprache. Ein aktuelles Handbuch zeitgenössischer Forschung